Corps Ѐtranger du Sigmoïde: À propos d’une Observation - KA, Ibrahima; Diop, Abib; Faye, Aliou Coly; Diop, Papa Saloum; Fall, Babacar (European Scientific Journal, ESJ, 2019)
The foreign bodies of the colon by the anal way are rare in our daily practice and constitute a taboo contrary to those ingested. These objects can be put into the rectum for therapeutic, sexual, behavioral disorder, to conceal the object (drugs) or more rarely, in accidental circumstances. They are very diverse and unusual. We report the case of a 66-year-old patient admitted to the emergency department for a foreign body in the sigmoid colon. X-ray of the abdomen without preparation showed the foreign body in the sigmoid. The extraction was done in trans anal, by medial laparotomy under umbilical. The postoperative course was simple. Les corps étrangers du côlon par voie anale sont rares dans notre pratique quotidienne et constituent un tabou contrairement à ceux ingérés. Ces objets peuvent être introduits dans le rectum à des fins thérapeutiques, sexuelles, par trouble du comportement, pour dissimuler l’objet (drogues) ou plus rarement, lors de circonstances accidentelles. Ils sont de nature très diverse et insolite. Nousrapportons le casrelativement rare dans notre pratique d’un patient de 66 ans reçu aux urgences pour corps étranger sigmoïdien. La radiographie de l’abdomen sans préparation montrait le corps étranger dans le sigmoïde. L’extraction a été faite en trans anale, par laparotomie médiane sous-ombilicale. Les suites opératoires étaient simples.